Teacher Empowerment Through Digital Literacy: Canva Training as Interactive Educational Media: Pemberdayaan Guru Melalui Literasi Digital: Pelatihan Canva Sebagai Media Edukatif Interaktif - Ruri Muhammad PD; Firdha Razak; Rustinah; A Zam Immawan Alam; Herman Alimuddin (Yayasan Ahmar Cendekia Indonesia, 2026)
In today’s digital era, teachers are required to be creative and adaptive to technological developments in order to support interesting and meaningful learning for students. Therefore, a hands-on practice-based training was conducted designed to improve teachers' competencies in designing teaching media using the Canva application, including visual materials, infographics, and interactive worksheets. The training method was carried out through a participatory workshop approach that actively involved teachers in the digital teaching media design process. This community service activity showed an increase in teachers' skills in creating Canva-based learning media. Canva training can improve teachers' skills in creating Canva-based learning media at SDN 32 Pulau Balang Caddi. Abstrak Di era digital saat ini, guru dituntut untuk kreatif dan adaptif terhadap perkembangan teknologi guna menunjang pembelajaran yang menarik dan bermakna bagi siswa. Oleh karena itu, dilakukan pelatihan berbasis praktik langsung yang dirancang untuk meningkatkan kompetensi guru dalam mendesain media ajar menggunakan aplikasi Canva, baik materi visual, infografis, maupun lembar kerja interaktif. Metode pelatihan dilakukan melalui pendekatan workshop partisipatif yang melibatkan guru secara aktif dalam proses perancangan media ajar digital. Melalui kegiatan pengabdian ini menunjukkan peningkatan terhadap keterampilan guru dalam membuat media pembelajaran berbasis Canva. Pelatihan Canva dapat meningkatkan keterampilan guru dalam membuat media pembelajaran berbasis Canva di SDN 32 Pulau Balang Caddi.